Predicting Iraqi Bank Customers Intentions To Use Digital Banking Services Through The Extended Theory Of Planned Behavior (TPB) - Sahi, Ala Mahdi (JURNAL ILMU MANAJEMEN SABURAI, 2024)
AbstractThe purpose of this study is to examine the determinants affecting Iraqi customers intentions to use of digital banking services based on the Extended Theory of Planned Behavior (TPB). Given that digital banking is a new concept in Iraq, understanding the key drivers behind its adoption is essential for the industry. This paper evaluates the impact of some variables, such as attitude, social pressure, and perceived behavioral control, trust, and perception value, on shaping customer adoption intention. The study used PLS-SEM with SmartPLS to interpret the data from a survey of 334 customers from Rafidain Bank, Rasheed Bank, and Trade Bank of Iraq selected using convenience sampling . Perceived value had the strongest effect on adoption intentions, followed by trust, social influence, and attitude. Perceived behavioral control did not have a significant effect on the intention to utilize digital banking services among consumers. These findings highlight the need to improve the perceived value and trust of digital banking platforms, as well as stimulate social influence to foster adoption. The minimal impact of perceived behavioral control showed that infrastructural hurdles and low digital literacy might also backburn individual confidence in using digital banking. In conclusion, this study significantly provides implications for Iraqi policymakers and the banking sector. This shifts the digital banking adoption efforts towards what banks will focus on developing an integrated system that is required for a radical transformation of financial systems within Iraq to allow more people to be banked by emphasizing boosting apparent value, trust-building, and social validation.Â Keywords: Digital banking , Theory of planned behavior , Iraqi bank sector